Great deaf Americans : the second edition - Moore, Matthew S., 1958-; Panara, Robert (Rochester, N.Y. : Deaf Life Press, 1996)
77 brief biographical profiles of eminent deaf people, past and contemporary, in a variety of fields, from aviation to teaching, represent the diversity of deaf identities in America, from culturally-Deaf to oral, from born-deaf to late-deafened.
Laurent Clerc -- Erastus "Deaf" Smith -- William Willard -- Edmund Booth -- John Carlin -- Laura Redden Searing -- Douglas Tilden -- Jueliette Gordon Low -- William E. "Dummy" Hoy -- William W. Beadell -- Thomas Scott Marr -- Cadwallader Washburn -- Luther "Dummy" Taylor -- George Hyde -- Regina Olson Hughes -- David Peikoff -- LeRoy Colombo -- Hillis Arnold -- Frances Woods -- Ernest Marshall -- Boyce R. Williams -- Cal Rodger, Nellie Zabel Willhite, Rhulin Thomas -- Art Kruger -- Robert Weitbrecht -- Frederick C. Schreiber -- Donald L. Ballantyne -- Roy Kay Holcomb -- Frances "Peggie" Parsons -- Martin L.A. Sternberg -- Marcella M. Meyer -- Andrew Foster -- Malcolm Norwood -- Bernard Bragg -- Morris Broderson -- Frank R. Turk -- Lowell Myers -- William Schyman -- Eugene Hairston -- Gertrude Scott Galloway -- Douglas J.N. Burke -- T.J. O'Rourke -- Robert Davila -- Alice Hagemeyer -- Frank Peter Hochman -- Jack R. Gannon -- Ernie Hairston -- Bonnie Poitras Tucker -- Judith Viera Tingley -- Henry Kisor -- Shirley J. Allen, Glenn B. Anderson -- I. King Joran, Jr. -- Phyllis Frelich -- Jack Levesque -- Linda Bove -- Kitty O'Neil -- Michael Chatoff -- John T.C. Yeh -- Chuck Baird -- Frank G. Bowe -- Julianna Fjeld -- Lou Ferrigno -- Bill Graham, Kathie Skyer Hering -- Mary Lou Novitsky -- Bruce Hlibok -- Marlee Matlin -- Jerry Covell, Tim Rarus, Greg Hlibok, Bridgetta Bourne-Firl -- Kenny Walker -- Shelley Beattie -- Curtis Pride -- Heather Whitestone -- Matthew Scott Moore, Robert F. Panara.
Includes bibliographical references (p. 476-507).
Keywords: Deaf -- United States -- Biography; Deaf; United States; Biography